Pengukuran Kinerja Dinas Pendapatan Daerah Provinsi Kalimantan Barat - Mustafa, Bob; Halim, Abdul (Jurnal Aplikasi Manajemen, 2009)
This research is aimed to know the performance of Local Income Office of West Borneo Province in local income management, its efficiency and effectiveness of activities, and public services. This research was using secondary data in which are the Report of Local Income Target and Realization of West Borneo Province period 2003-2007, Performance Accountability Report of Local Income Official of West Borneo Year 2007, and PDRB of West Borneo Province period 2003-2007. Besides, it was completed by primary data obtained from questionnaire distributed to service users of Kantor Bersama SAMSAT Pontianak 1 and interview with officials in Local Income Office of West Borneo Province related to local income management and public services. PAD’s growth ratio, contribution of local taxes and local retributions on PAD, PAD’s elasticity on PDRB, level of fiscal decentralization, PAD’s effectiveness ratio, efficiency and effectiveness of activity ratio, and People Satisfaction Index become tool of data analyzing that used in measuring performance of Local Income Office of West Borneo Province. The result shows that: (1) PAD experiences positive and stable growth, (2) local taxes still dominate in PAD’s revenue, (3) Local Government of West Borneo Province has a good structure of PAD which marked with elasticity in growth of PAD toward PDRB’s growth, (4) financial ability of West Borneo Province in funding government and local development is categorized good, (5) ability of Local Income Office in realizing or mobilizing PAD according to target is categorized effective, (6) activities of Local Income Office year 2007 have been effectively and efficiently done, (7) performance of public services in Kantor Bersama SAMSAT Pontianak 1 is categorized good. Keywords: performance measurement, local genuine income (PAD), efficiency and effectiveness of activities, and public services